Hubungan Kadar 25(OH)D3 dengan Lingkar Betis Pada Kelompok Lanjut Usia di Panti Santa Anna: Studi Potong-Lintang - Alexander Halim Santoso; Susi Olivia Lontoh; Yohanes Firmansyah; Giovanno Sebastian Yogie; Daniel Goh; Andini Ghina Syarifah; Stanislas Kotska Marvel Mayello Teguh; Anthon Eka Prayoga Khoto (Universitas Malahayati Lampung, 2024)
ABSTRACT The research on vitamin D is still developing until its role in the immune system, the absorption of phosphate from the intestine, and preventing its excretion in the kidneys are known. The prevalence of low levels of vitamin D is high, and recently, it was discovered that there was a relationship between vitamin D deficiency and the incidence of sarcopenia in the elderly. Determining vitamin D levels and the incidence of sarcopenia in the elderly at the Santa Anna Nursing Home. This study was an analytical study with a cross-sectional design conducted on elderly residents of the Santa Anna Nursing Home in July 2023 to assess vitamin D levels and calf circumference to assess sarcopenia. The data obtained were analyzed using Mann-Whitney. Result Of the 32 respondents, the average age was 72.66 years, and 22 (68.7%) respondents were women. It was found that 30 (93.8%) respondents experienced vitamin D deficiency, and 15 (46.9%) respondents experienced sarcopenia. The results of statistical tests showed that there was no difference in the mean levels of vitamin D between the sarcopenic and non-sarcopenic groups. However, the group of patients with sarcopenia had vitamin D levels that tended to be lower compared to the group without sarcopenia (18 vs. 21 ng/mL; MR 15.50 vs. 17.38). There was no statistically significant difference in mean vitamin D levels between the groups with and without sarcopenia. However, there is a tendency for groups of patients with sarcopenia to have vitamin D levels that tend to be lower than those in groups without sarcopenia. Keywords: Vitamin D, Sarcopenia, Elderly ABSTRAK Hingga saat ini, penelitian terhadap vitamin D terus berkembang hingga diketahui perannya dalam sistem imun, absorpsi fosfat dari usus dan mencegah terekskresinya pada ginjal. Tingginya prevalensi kurangnya kadar vitamin D dan baru-baru ini, diketahui ada hubungan defisiensi vitamin D dengan kejadian sarkopenia pada lansia. Mengetahui kadar vitamin D dengan kejadian sarkopenia pada lansia di Panti Werda Santa Anna. Penelitian ini adalah analitik dengan desain potong lintang yang dilakukan pada lansia penghuni Panti Werdha Santa Anna pada Juli 2023 untuk menilai kadar vitamin D dan lingkar betis untuk menilai sarkopenia. Data yang didapat kemunian dianalisis menggunakan Mann-Whitney. Didapat 32 responden dengan rerata usia 72,66 tahun dan sebanyak 22 (68,7%) responden adalah perempuan. Didapat 30 (93,8%) responden mengalami defisiensi vitamin D dan 15 (46,9%) responden mengalami sarkopenia. Hasil uji statistic didapat hasil tidak terdapat perbedaan rerata kadar vitamin D antara kelompok sarkopenia dan tidak. Namun dapat terlihat bahwa kelompok pasien dengan sarkopenia memiliki kadar vitamin D yang cenderung lebih rendah dibandingan dengan kelompok tanpa sarkopenia (18 vs 21 ng/mL; MR 15,50 vs 17,38). Tidak terdapat perbedaan rerata kadar vitamin D yang bermakna secara statistik antara kelompok dengan atau tanpa sarkopenia. Namun terdapat kecenderungan kelompok pasien dengan sarkopenia memiliki kadar vitamin D yang cenderung lebih rendah dibandingan dengan kelompok tanpa sarkopenia. Kata Kunci: Vitamin D, Sarkopenia, Lanjut Usia